PROTOTIPE KNOWLEDGE MANAGEMENT SYSTEM DENGAN MENGGUNAKAN METODE KMD DAN SECI - Fauziah . (FKOM UNIKU, 2015)
AbstractIn the world of education, we need some understanding about learning process between teacher and students. A teacher as educator is demanded to be able to communicate to the students using konvensional or infromation technology media. The teacher can use Knowledge management from the school in the learning process. Knowledge management gives solution from the knowledge management system so that the students at school can improve their skills without any boundaries. Penelitian ini is to find a model of Knowledge management system which is suitable for the needs of students of SMA Pertiwi. The system applied by teachers has the same goals among teachers now or in the next future. Teachersâ€™ knowledgeÂ influence the learning process at school. This research uses Data Analysis System from Knowledge Management Diagnostic from Bukowitz and SECI from Nonaka. I also use desain using UML and Framework CI. Analysis of test result dan the prototipe used at school will make the learning process more effective and efficient especially in the knowledge management system for sharing knowledge.